Ingrid mamma felice e Sophia nei guai: maternità, divismo e scandali mediali sulle pagine di «Oggi » 1949-1959 (Schermi. Storie e culture del cinema e dei media in Italia, 2020)
This essay is an examination of two famous star scandals of the Fifties: the extramarital affair of Ingrid Bergman with Roberto Rossellini and that of Sophia Loren with Carlo Ponti. Focusing on the Italian popular magazine «Oggi»’s coverage of these stars’ scandals, my article aims to investigate popular discourses of sexuality and motherhood in relation to historical and social change in postwar Italy, in particular the interconnectedness of media scandals, star’s textual and extratextual images, and the symbolic construction of motherhood.
Keywords: Ingrid Bergman; Sophia Loren; star scandals; motherhood